Personal values and identity structures of Malay and Chinese entrepreneurs in Malaysia - Hussin, Habruzah (Cranfield University, 1995)
The research involves a cross-cultural exploratory research on personal values and identity structures of Malay and Chinese entrepreneurs as reflected in their cognitive functioning. The general focus of this research is to study personal values through indirect measures, as emerging constructs elicited from cognitive activities. This study adopts a different approach in that it moves away from the search for a single set of entrepreneurial traits. On the other hand, examining the personal values of entrepreneurs can be more fruitful. In this context, it is assumed that entrepreneurs undergo changes in personal values and identity due to changes in their personal and social situations. This research integrates nomothetic' (perspective of the general) and 'idiographic' (perspective of the particular) research methods. The techniques of data collection used are in-depth interviews, demographic data questionnaire, and Identity Structure Analysis. The data gathered were analysed using three different techniques namely quantitative and qualitative account analysis, statistical analysis using SPSS, and Identity Exploration (IDEX- IDIO and IDEX-NOMO) computer programs. The research reveals fifteen personal values common to Malay and Chinese entrepreneurs: 'personal independence, trustworthiness, a comfortable life, frugality, perseverance, hard work utilise and create opportunities, benevolence, versatility, fatalism, risk taking, self discipline, innovativeness, mutual obligation and reciprocity to family and kinship and high achievement'. The single personal value found specific to Malay entrepreneurs is 'religious piety'. On the other hand, the personal values revealed to be specific to Chinese entrepreneurs are 'sustaining growth and continuity as family business' and 'harmonious relationships with others'. The findings from this study show that there are similarities and differences in the identity structures between both groups of entrepreneurs. Most Malay and Chinese entrepreneurs have a high level of 'idealistic identification' with 'admired person', 'successful entrepreneur', and 'most Chinese entrepreneurs'. Chinese entrepreneurs sampled in this study have a 'moderate' level of 'idealistic identification' with Malay entrepreneurs. Malay entrepreneurs have a 'moderate' level of 'idealistic identification' with their 'father' whereas Chinese entrepreneurs' identification can be considered 'high'. Both groups of entrepreneurs have high self-confidence with regard to their roles as 'an entrepreneur', 'as a husband', and 'as a Malay/ Chinese'. This research has made considerable contribution to knowledge specifically in the field of entrepreneurial studies. This empirical research into personal values of entrepreneurs in general and in particular the linkage with entrepreneur's identity and role expectations broadened the psychological perspective of entrepreneurs. It is reasonable to qualify this research as one of the very few studies into personal values and identity structures of entrepreneurs. More specifically this is the first empirical research not only to compare personal values and identity of Malay and Chinese entrepreneurs but also Malay entrepreneurs in general. The study of personal values and identity of entrepreneurs is still in its infancy. Therefore, further research should be conducted to enrich existing knowledge in this area.